Evolutionary origins of music. Classical and recent hypotheses - Kalinowski, Kasper; Kozłowska, Agata; Malesza, Marta; Danel, Dariusz P. (Anthropological Review, 2021)
The aim of this paper is to review recent hypotheses on the evolutionary origins of music in Homo sapiens, taking into account the most influential traditional hypotheses. To date, theories derived from evolution have focused primarily on the importance that music carries in solving detailed adaptive problems. The three most influential theoretical concepts have described the evolution of human music in terms of 1) sexual selection, 2) the formation of social bonds, or treated it 3) as a byproduct. According to recent proposals, traditional hypotheses are flawed or insufficient in fully explaining the complexity of music in Homo sapiens. This paper will critically discuss three traditional hypotheses of music evolution (music as an effect of sexual selection, a mechanism of social bonding, and a byproduct), as well as and two recent concepts of music evolution - music as a credible signal and Music and Social Bonding (MSB) hypothesis.